Evaluation of Corporate Archive Management System: A Case Study At PT Surabaya Industrial Estate Rungkut In 2025 - Afiyah Yasmin Nabilla; Ikhwan Kholid (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to evaluate the archive management system implemented at PT Surabaya Industrial Estate Rungkut (PT SIER), a state-owned enterprise managing industrial areas in Indonesia. The research employed a qualitative descriptive approach involving field observation, interviews with archive personnel, and documentation analysis. Findings indicate that PT SIER’s current archive management system is predominantly manual, lacks integration with digital technology, and suffers from unstructured classification practices. Major internal constraints include limited qualified human resources and the absence of standardized archival procedures. External constraints involve inadequate storage facilities, leading to disorganized document placement and increased risk of physical damage. The study also found that document retrieval is inefficient due to reliance on a single archive officer and the absence of systematic indexing. Based on these findings, the study recommends the implementation of an integrated digital archival system, the development of Standard Operating Procedures (SOPs), and regular training for employees to enhance document classification and indexing. These measures are expected to improve the efficiency and reliability of PT SIER’s archival practices.